Implementasi Diversifikasi Konsumsi Pangan Lokal dan Faktor-faktor Yang Mempengaruhinya dalam Menu Keluarga untuk Menunjang Ketahanan Pangan - Heryadi, D.Yadi; Rofatin, Betty; Tedjaningsih, Tenten; Nurcahya, Intan (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Diversification based on local food is the most feasible alternative to increase food security. Currently the dominant food consumed by the people of Tasikmalaya city is rice with consumption/capita/month of 8.25 kg, so it requires 5,964 tons per month. Only 73.50 percent can be fulfilled by yourself, the rest is imported from outside the region. Until now, it is not yet known whether families in Tasikmalaya City have diversified local food-based consumption into their daily menus in order to reduce dependence on rice. The specific aim of this research is to determine the implementation of diversification of local food consumption and the factors that influence it in the family menu to support food security. The research method used a survey of households in Tasikmalaya City with a sample size of 100 households from 170,486 households in Tasikmalaya City. Sampling used the Slovin method and applied proportional random sampling in 10 sub-districts in Tasikmalaya City. The data used consists of primary data and secondary data. Data analysis use descriptive and multiple regression analysis. The research results show that of the 100 household respondents studied, 31 percent regularly consume it, 59 percent of respondents only consume it on certain occasions and 10 percent never consume local food in their daily menu. Meanwhile, simultaneously the variables Household Characteristics, Income, Knowledge, Tastes about Rice, influence Implementation. Meanwhile, partially only characteristics have a significant effect on implementation, while other variables have no effect on implementation.